(3TeS GdYdhe hOhGA cdGe GdYQH ef Gdcdhes - (3fThGf Hf SYjO GdMejQj, CHh SYjO,J (B573 (3g` s
(3ChdgG (B:s
(3HGH GdOGd hGdMGA heG HYOgeG (B: (3GdCSeGA (B: (3aYd , HaJM GdaGA , hSchf GdYjf V (B: (3OMV eYLeI Ci Rdb , bGd hMGO ceG MGO GdHYjQ Yf GdOMV d(B: (3GdOMd (B: (3KbH Vjb , eJSY CSadg s
(3BNQgG (B:s
(3aYd HGdcSQ , jaYd HGdaJM GdTCR HGdRGi Gdbdb Tjag TCakG hTGakG CHZVg , hTja QMdg hTjaJ EPG NQL ajgG GdTGaI s
(3GdNW eged GdfbW CMjGfkGs
(3cJHJ GdYfhGfGJ HGdMeQIs
(3hYdi MhGTjgG ebGHdGJs
(3GdfSNI HgG MhGT s
(3HgG JbWjY GdHYV GdChQGb s
(3fSNI KGefI s
Keywords: (3GddZIs